Marine-Derived Collagen as Biomaterials for Human Health - Xu, Ning; Peng, Xue-Liang; Li, Hao-Ru; Liu, Jia-Xuan; Cheng, Ji-Si-Yu; Qi, Xin-Ya; Ye, Shao-Jie; Gong, Hai-Lun; Zhao, Xiao-Hong; Yu, Jiangming; Xu, Guohua; Wei, Dai-Xu (Frontiers in Nutrition, 2021)
Collagen is a kind of biocompatible protein material, which is widely used in medical tissue engineering, drug delivery, cosmetics, food and other fields. Because of its wide source, low extraction cost and good physical and chemical properties, it has attracted the attention of many researchers in recent years. However, the application of collagen derived from terrestrial organisms is limited due to the existence of diseases, religious beliefs and other problems. Therefore, exploring a wider range of sources of collagen has become one of the main topics of researchers. Marine-derived collagen (MDC) stands out because it comes from a variety of sources and avoids issues such as religion. On the one hand, this paper summarized the sources, extraction methods and characteristics of MDC, and on the other hand, it summarized the application of MDC in the above fields. And on the basis of the review, we found that MDC can not only be extracted from marine organisms, but also from the wastes of some marine organisms, such as fish scales. This makes further use of seafood resources and increases the application prospect of MDC.